EVALUASI KARAKTERISTIK BATUBARA SUB BITUMINUS INDONESIA DENGAN PROSES NEDOL - Yusnitati Yusnitati (Jurnal Energi dan Lingkungan (Enerlink), 2005)
A characterization of coal liquid derived from liquefaction of bituminous coal from Indonesia was conducted. As synthetic oil from coal requires further treatment to improve its quality so that could meet a specific market need. One of few techniques in improving the coal oil is through hydrotreatment process by reducing its nitrogen, sulfur, oxygen and aromatics contents. Experiment using small-scale fixed bed reactor shows that there is an improvement in quality of recycle solvent used for coal liquefaction after first hydrotreatment. Coal slurry using first hydrotreated oil as solvent shows lower viscosity than that of non- hydrotreated oil, and if mixed with Banko coal, the coal concentration could achieve as high as 50%. Nitrogen and sulfur contents in hydrotreated oil are reduced to negligible level and the storage stability is remarkably improved after hydrotreatment. The quality of fuel from second hydrotreatment is still lower than that of petroleum productc in terms of ‘cetane number’, ‘smoke point’, contents of sulfur and aromatics.Kata kunci: Hydrotreatment, banko coal, fixed bed reactor, synthetic oil